Pelacakan Secara Imunohistokimiawi Antigen Ekskretori-Sekretori pada Sapi Bali yang Terinfeksi Fasciola gigantica (IMMUNOHISTOCHEMICAL DETECTION OF EXCRET0RY-SECRETORY ANTIGENS IN BALI CATLLE INFECTED BY FASCIOLA GIGANTICA) - Winaya, Ida Bagus Oka; Astawa, I Nyoman Mantik; Damriyasa, I Made; Dharmawan, Nyoman Sadra; Berata, I Ketut (Jurnal Veteriner, 2014)
In order to study the distribution of excretory-secretory (ES) F. gigantica in liver tissue of infected balicattle a research was establisihed using monoclonal antibodies (mAbs) againts ES antigens. Immortalmouse myeloma cells were fused with the lymphocytes derived from the spleen of mice that immunizedwith ES antigen. The mAbs were tested for their specificity by using enzyme linked immunosorbent assay(ELISA). Five specific mAbs againts ES antigens were isolated and two mAbs were used for immunodetectionof ES antigens in liver tissue of bali cattle. Immunohistochemical ES antigens were not detected in paraffinembeded tissue of negative confirmed fasciolosis samples. ES antigens was detected in hepatocytes andcytoplasm of bile duct epithelims in the bali cattle that infected with fasciolosis in moderate intensity.Therfore indicated that mAbs produced in this study are applicable for detecting ES antigens in bali cattleinfected by F. gigantica.
Keywords: excretory-secretory antigens, F. gigantica, mAbs, Bali cattle